Pendidikan Akhlaq Aplikatif-Integratif pada Madrasah Ibtidaiyah di Rubaru Sumenep - Ummi Kulsum (Sekolah Tinggi Ilmu Tarbiyah (STIT) Aqidah Usymuni, 2020)
Education of moral is education that is very important to instill moraland spiritual values in life that can foster character, behavior, and good moralsfor future. If education of moral is not instilled in students from an early age, itdoes not close the possibility that students will fall into something that is notdesired by the wider community. Research on